PENGARUH EKSTRAK BROTOWALI (Tinospora crispa L.) TERHADAP FERTILITAS MENCIT (Mus musculus L. SWISS WEBSTER) BETINA - Arofiki, Afdal Hasbi (Pendidikan Biologi, 2014)
Brotowali is a traditional medicine plants have potential as contraception. The active substance from Brotowali is Alkaloid, that have antiproliferative in reproduction cell. This aimed is research to find out the Effects of Brotowali extract (Tinospora crispa L.) in female mice (Mus musculus L., Swiss Webster) fertility. This research is experiment research used completelly randomized design with 4 treatments and 6 replication. The treatments are Brotowali extract, as P1, a dose of 5x10-2 (P2), 6x10-2 (P3) and 7x10-2 (P4) gram/mice. This research was conducted in January 2014 in Zoology Laboratory of Biology FMIPA UNP. The Parameter observed the 0 day of pregnant, length of pregnancy and the number of living pup of mice. The data from the 0 day of pregnant is treated by the continued examination by using LSD at p<0,05. The data of pregnant and the number of pup mice continued by Duncan Multiple Range Test (DNMRT) at p<0,05. The result shows that Brotowali extract (p<0,05) decreased of sum of pup and the day of 0 pregnant. Otherwise, Brotowali extract does not influence the length of pregnant. It can concluded that, Brotowali extract decreased in female mice fertility